Desain Pembelajaran Berbasis Ketuntasan Kitab Di Madrasah Diniyah Al-Mardliyah Pamekasan - Holik, Abdul; Ridho, Ali; Listiana, Heni; Kholili, Ach. (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
In the realm of education, kitab (Islamic text) material is crucial for students as it serves as both a foundation and provision for their religious understanding. In this context, Madrasah Diniyah Al-Mardliyah addresses this by designing a learning approach based on kitab mastery. This learning method is primarily aimed at ensuring that every student not only comprehends the kitab material but also masters it deeply in accordance with the established curriculum. Therefore, this study focuses on kitab mastery learning and its advantages and disadvantages at Madrasah Al-Mardliyah Pamekasan. Through observation, interviews, and documentation, the following data were obtained: The principles of learning at Madrasah Diniyah Al-Mardliyah include in-depth understanding, continuous evaluation, as well as remedial and enrichment programs. The learning process encompasses orientation, presentation, structured exercises, guided exercises, and independent exercises, with evaluation conducted through the Sorogan and Tamrin systems. The advantages of kitab mastery learning include enhancing learning efficiency, providing equal opportunities, and fostering positive attitudes among students. However, its drawbacks are that it requires a long time, professional teachers, and high operational costs. This madrasah has successfully implemented mastery learning through detailed planning, the application of various teaching methods, and regular evaluations.